Organization capital and mergers and acquisitions - Li, Kai (2019)
Using a sample of completed U.S. acquisition deals over the period 1984–2014, we find that acquirer organization capital as measured by capitalized selling, general, and administrative (SG&A) expenses is associated with superior deal performance. We show that high organization-capital acquirers achieve significantly higher abnormal announcement period returns, and better post-merger operating and stock performance, than low organization-capital acquirers. Additional tests suggest a causal relation between acquirer organization capital and deal performance. We further show that post-merger, high organization-capital acquirers cut more on the cost of goods sold, invest more in SG&A expenses, and achieve greater asset turnover and innovative efficiency.